Evaluation of Bontang City Government Policies to Improve the Regional Investment Climate - Amriadi, Amriadi; Saipul, Saipul; Prakoso, Cathas Teguh (Jurnal Pemerintahan dan Politik Lokal, 2025)
This study evaluates the effectiveness, competitiveness, and responsiveness of the Bontang City Government’s policies in improving the regional investment climate within the framework of economic diversification. The research employs a qualitative descriptive-evaluative method, which combines policy evaluation and interpretive analysis to assess how investment-related programs are implemented and how stakeholders perceive their outcomes. Data were collected through documentation, observation, and interviews with government officials, business actors, and community representatives, then analyzed using the six evaluation criteria proposed by William N. Dunn—effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. Findings indicate that although Bontang has made significant progress through the implementation of the Online Single Submission (OSS) system, the establishment of the Public Service Mall, and the enactment of Regional Regulation No. 1 of 2017 on Investment, various structural barriers remain. Bureaucratic inefficiency, weak inter-agency coordination, limited investment promotion, and insufficient human resource capacity hinder policy outcomes and reduce investor confidence. Moreover, policy responsiveness is still concentrated on the oil and gas sector, with less attention given to emerging industries such as tourism, creative economy, and renewable energy. The study concludes that an adaptive and integrated governance model is essential to ensure that investment policy effectively supports sustainable and inclusive regional economic transformation